A pathway to understanding cinema in Peru or a way in which films portray the Peruvian social being episodically - De la Cruz Villanueva, Carlos (2023)
The interest of these pages is to cover a part of the cinema activity in Peru, until the end of the first half of the 20th century. Achieving with this to observe his activity and understand how in his actions he reproduces various events of our Peruvian society considered as events, many of them formed in daily life, which are recreated in audiovisual fiction and make it possible to contribute to the composition of the social memory. For this, we will make use of an elementary historical description and establish a perimeter approximation to its dynamics over time. Using a category that will allow us an elementary understanding of what we consider to be an event, a category that allows us to understand a social dynamic, be it outstanding or underlying everyday life.